Blood cytokine patterns suggest a modest inflammation phenotype in subjects with long‐chain fatty acid oxidation disorders. Issue 6 (25th March 2019) - McCoin, Colin S.; Gillingham, Melanie B.; Knotts, Trina A.; Vockley, Jerry; Ono‐Moore, Kikumi D.; Blackburn, Michael L.; Norman, Jennifer E.; Adams, Sean H.
Abstract: Excessive cellular accumulation or exposure to lipids such as long‐chain acylcarnitines (LCACs), ceramides, and others is implicated in cell stress and inflammation. Such a situation might manifest when there is a significant mismatch between long‐chain fatty acid (LCFA) availability versus storage and oxidative utilization; for example, in cardiac ischemia, increased LCACs may contribute to tissue cell stress and infarct damage. Perturbed LCFA β ‐oxidation is also seen in fatty acid oxidation disorders (FAODs). FAODs typically manifest with fasting‐ or stress‐induced symptoms, and patients can manage many symptoms through control of diet and physical activity. However, episodic clinical events involving cardiac and skeletal muscle myopathies are common and can present without an obvious molecular trigger. We have speculated that systemic or tissue‐specific lipotoxicity and activation of inflammation pathways contribute to long‐chain FAOD pathophysiology. With this in mind, we characterized inflammatory phenotype (14 blood plasma cytokines) in resting, overnight‐fasted ( 10 h), or exercise‐challenged subjects with clinically well‐controlled long‐chain FAODs ( n = 12; 10 long‐chain 3‐hydroxyacyl‐CoA dehydrogenase [LCHAD]; 2 carnitine palmitoyltransferase 2 [CPT2]) compared to healthy controls ( n = 12). Across experimental conditions, concentrations of three cytokines were modestly but significantly increased in FAOD (IFN γ, IL‐8, and MDC), and plasma levels of IL‐10 (considered an inflammation‐dampening cytokine) were significantly decreased. These novel results indicate that while asymptomatic FAOD patients do not display gross body‐wide inflammation even after moderate exercise, β ‐oxidation deficiencies might be associated with chronic and subtle activation of "sterile inflammation." Further studies are warranted to determine if inflammation is more apparent in poorly controlled long‐chain FAOD or when long‐chain FAOD‐associated symptoms are present. Abstract : It is possible that limited or incomplete fatty acid catabolism caused by inherited disorders of mitochondrial beta‐oxidation leads to accumulation of lipid metabolites that cause cell dysfunction and inflammation. To examine this postulate, blood cytokines were compared between controls and participants with long‐chain fatty acid oxidation disorders; only very modest increases in select cytokines were observed at rest, postprandially and following an exercise bout. The results indicate that loss of efficient fatty acid oxidation does not manifest with clinically relevant inflammation in well‐controlled patients, but it remains to be seen if lipotoxicity occurs episodically in conjunction with other illness or during periods of excessive fat mobilization and body stress.